The Ex vivo Eye Irritation Test (EVEIT) model as a mean of improving venom ophthalmia understanding. (August 2018) - Delafontaine, Marie; Panfil, Claudia; Spöler, Felix; Kray, Stefan; Burgher, François; Mathieu, Laurence; Blomet, Joël; Schrage, Norbert F.; Tambourgi, Denise V.
Abstract: Snakes belonging to the genus Naja (Elapid family), also known as "spitting cobras", can spit venom towards the eyes of the predator as a defensive strategy, causing painful and potentially blinding ocular envenoming. Venom ophthalmia is characterized by pain, hyperemia, blepharitis, blepharospasm and corneal erosions. Elapid venom ophthalmia is not well documented and no specific treatment exists. Furthermore, accidental ejection of venom by non-spitting vipers, as Bothrops, also occurs. The Ex vivo Eye Irritation Test model (EVEIT) has enabled important progress in the knowledge of chemical ocular burns. Considering the lack of experimental animal model, we adapted the EVEIT to study venom ophthalmia mechanisms. Ex vivo rabbit corneas were exposed to venoms from spitting ( Naja mossambica, Naja nigricollis ) and non-spitting ( Naja naja, Bothrops jararaca and Bothrops lanceolatus) snakes, and rinsed or not with water. The corneal thickness and the depth of damage were assessed using high-resolution optical coherence tomography (HR-OCT) imaging and histological analysis. All Naja venoms induced significant corneal edema, collagen structure disorganization and epithelial necrosis. Corneas envenomed by African N. mossambica and N. nigricollis venoms were completely opaque. Opacification was not observed in corneas treated with venoms from non-spitting snakes, such as the Asian cobra, N. naja, and the vipers, B. jararaca and B. lanceolatus. Moreover, Bothrops venoms were able to damage the epithelium and cause collagen structure disorganization, but not edema. Immediate water rinsing improved corneal status, though damage and edema could still be observed. In conclusion, the present study shows that the EVEIT model was successfully adapted to set a new experimental ex vivo animal model of ophthalmia, caused by snake venoms, which will enable to explore new therapies for venom ophthalmia. Highlights: Ex vivo Eye Irritation Test (EVEIT) was successfully adapted to set a new ex vivo animal model of snake venom ophthalmia. The EVEIT model reproduces the corneal opacification observed in case of African Elapid venom ophthalmia. Improvement of the corneal status, after envenomation, could be achieved by immediate water decontamination.